MENGUKUR KINERJA DESENTRALISASI ADMINISTRASI DI KOTA KUPANG - I Putu Yoga Bumi Pradana (NATAPRAJA, 2019)
This article aims to analyze the performance of the local government of the City of Kupang in carrying out administrative decentralization from the perspective of public service quality and community satisfaction surveys in the city of Kupang. This study uses descriptive qualitative methods and data collection was carried out through observation, surveys, interviews, and findings from literature studies, as well as secondary data studies. Informants from this study include, employees of the Population and Civil Registry Office, the Investment and One-Stop Integrated Services Office, and the Kupang City Lerik SK Hospital. In addition, there were 120 respondents to measure SKM in the field of cleanliness and clean water services in six districts of Kupang City which were determined using accidental sample techniques. The results showed the fact that the value of service quality in the area of population and health is still categorized as C or not good while in the one-stop integrated service sector it has a value of B or good. While the results of the community satisfaction survey show that only the health and integrated one-door services are categorized as good while the population, cleaning and water services are categorized as poor.